2016
DOI: 10.1016/j.biocon.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Trade in live reptiles, its impact on wild populations, and the role of the European market

Abstract: Of the 10,272 currently recognized reptile species, the trade of fewer than 8% are regulated by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the European Wildlife Trade Regulations (EWTR). However, the International Union for Conservation of Nature (IUCN) Red List has assessed 45% of the world's reptile species and determined that at least 1390 species are threatened by “biological resource use”. Of these, 355 species are intentionally targeted by collectors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
160
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 83 publications
0
160
0
1
Order By: Relevance
“…In particular, we found that noncompliance among EU respondents (excluding the UK) was significantly more likely, supporting findings that the EU is a destination for smuggled wildlife (Auliya et al . ), potentially due to variable enforcement between Members States (Reeve ). Specific weak points of entry to the EU for orchids and for other CITES taxa should be identified, and the best ways to address these enforcement gaps assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we found that noncompliance among EU respondents (excluding the UK) was significantly more likely, supporting findings that the EU is a destination for smuggled wildlife (Auliya et al . ), potentially due to variable enforcement between Members States (Reeve ). Specific weak points of entry to the EU for orchids and for other CITES taxa should be identified, and the best ways to address these enforcement gaps assessed.…”
Section: Discussionmentioning
confidence: 99%
“…are particularly at risk, with many species threatened with extinction due to collection or trade (IUCN 2015). These factors make the orchid trade analogous in many ways to other wildlife trades, such as those with parallel legal and illegal markets (e.g., fur: Wyatt 2009; reptiles: Auliya et al 2016) and those with coexisting mainstream and specialist consumers (e.g., songbirds: Jepson & Ladle 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Locations are mapped to the nearest 2×2 km square representing groups of islands in the Grenadines. We have deliberately avoided being specific to protect the animals (see Auliya et al 2016). Note that there are alien iguanas on some islands and not all of the island clusters shown here have purebred populations of Iguana insularis insularis.…”
Section: Systematic Analysismentioning
confidence: 99%
“…Reptiles are widely considered as a highly threatened vertebrate group, with an estimate of nearly 18.9% of global species at risk of extinction (Böhm et al 2013). Reptiles, particularly snakes, have been hunted for individual and commercial use due to their medicinal and nutritional value, and are still being killed indiscriminately in large numbers (Böhm et al 2013, Auliya et al 2016. Consequently, human exploitation has become a serious threat to snake populations in many parts of the world (Todd et al 2010), leading to their decline or even extinction (Zhou and Jiang 2004, Brooks et al 2007, Nijman 2010, Natusch and Lyons 2012, Sasaki et al 2012).…”
Section: Introductionmentioning
confidence: 99%